Effect of the intrasession exercise order of flywheel resistance and high-intensity interval training on maximal strength and power performance in elite team-sport athletes - Petré, H.; Ovendal, A.; Westblad, N.; Ten Siethoff, L.; Rosdahl, H.; Psilander, N. (The Journal of Strength and Conditioning Research, 2023)
This study aimed to investigate the effect of intrasession exercise order of maximal effort flywheel resistance training (RT; 4 × 6 repetitions [rep]) and high-intensity interval training (HIIT, 2-4 × 8 rep of 20 second at 130% of Watt at V?o2max [wV?o2max]), on the development of maximal strength and power in elite team-sport athletes. A 7-week training intervention involving 2 training sessions per week of either HIIT followed by RT (HIIT + RT, n = 8), RT followed by HIIT (RT + HIIT, n = 8), or RT alone (RT, n = 7) was conducted in 23 elite male bandy players (24.7 ± 4.3 years). Power and work were continuously measured during the flywheel RT. Isometric squat strength (ISq), countermovement jump, squat jump, and V?o2max were measured before and after the training period. Power output during training differed between the groups (p = 0.013, n²_p = 0.365) with RT producing more power than HIIT + RT (p = 0.005). ISq improved following RT + HIIT (~80%, d = 2.10, p = 0.001) and following HIIT + RT (~40%, d = 1.64, p = 0.005), and RT alone (~70%, d = 1.67, p = 0.004). V?o2max increased following RT + HIIT and HIIT + RT (~10%, d = 1.98, p = 0.001 resp. d = 2.08, p = 0.001). HIIT before RT reduced power output during RT in elite team-sport athletes but did not lead to blunted development of maximal strength or power after a 7-week training period. During longer training periods (>7-weeks), it may be advantageous to schedule RT before HIIT because the negative effect of HIIT + RT on training quality increased during the final weeks of training. In addition, the largest training effect on maximal strength was observed following RT + HIIT.